THE EFFECT OF STATE OWNERSHIP ON FIRM VALUE AND ITS IMPLICATIONS IN THE INDONESIAN CAPITAL MARKET - Faisal Akbar; Taufik; Nyimas Dewi Murnila Saputri; Fida Muthia (Journal of Applied Digital Business Management, 2025)
This research examines how government ownership (GOVi) affects firm value (PBV) among state-owned enterprises traded on the Indonesia Stock Exchange throughout the period from the first quarter of 2020 to the first quarter of 2021. To enhance the robustness of the model, firm size and firm growth are incorporated as control variables. The research employs secondary data obtained from publicly available financial reports published by the IDX. Using purposive sampling, twelve state-owned firms were selected as the final sample. The analysis was conducted using panel data linear regression through Eviews software. The findings indicate that government ownership (GOVi) exerts a positive and statistically significant influence on firm value (PBV). Conversely, firm size shows no measurable effect on firm value, and firm growth likewise demonstrates no significant association with PBV.